2020
DOI: 10.1021/acs.jpcc.0c04512
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Adsorption States of TNT and DNAN on Corundum and Hematite

Abstract: Adsorption isotherms are a critical tool in determining the transport of environmental contaminants through a particular media. Owing to the inherent heterogeneity of soils, the determination of which soil components are responsible for the adsorption and retention of a particular contaminant remains a challenge. In the current study, we consider several thermodynamic adsorption states in order to predict whether or not 2,4,6-trinitrotoluene (TNT) or 2,4-dinitroanisole (DNAN) would be either a ground-water con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(29 citation statements)
references
References 49 publications
0
28
1
Order By: Relevance
“…The thermal corrections were then added to the DFT energies from the finite difference calculations. This setup gave errors in the binding energy less than 0.1 eV, and gave nearly a magnitude in terms of speed-up …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The thermal corrections were then added to the DFT energies from the finite difference calculations. This setup gave errors in the binding energy less than 0.1 eV, and gave nearly a magnitude in terms of speed-up …”
Section: Methodsmentioning
confidence: 99%
“…Our binding energies ( E BE ) were calculated in the usual fashion, i.e., where E dopamine+surface is the total energy of the adsorbate and oxide surface, E dopamine is the gas-phase adsorbate energy, and E surface is the energy of the bare oxide surface. In order to translate this into surface coverages of the individual concrete components, we follow our recent methodology by starting with the Boltzmann distribution where Δ G BE, i is the Gibbs free energy of binding for component i . Here, Δ G BE, i is defined similarly to eq where we replace the electronic energies with the Gibbs free energies.…”
Section: Computational Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…Throughout the last several years, our group has extensively examined Munition interactions with components of natural water and components of arid soil. These computational studies have demonstrated several important factors in how these compounds are affected by the environment, including the solvation of munitions, decoupling interactions between various environmental components (e.g., studies on individual soil components), optical spectra, and degradation (vide supra). Further detailed analysis requires solutions that will allow for interactions between environmental components while simultaneously reducing empiricism.…”
Section: Introductionmentioning
confidence: 99%